Association of Left Atrium Remodeling With Major Adverse Cardiovascular Events in Asymptomatic Type 2 Diabetes Patients With Early Chronic Kidney Disease - Mingxia Gong; Min Xu; Suoya Pan; Shu Jiang; Xiaohong Jiang (Reviews in Cardiovascular Medicine)
Background: This study aimed to use four-dimensional automatic left atrial quantification (4D Auto LAQ) to quantitatively evaluate the morphological and functional changes in the left atrium (LA) in asymptomatic type 2 diabetes mellitus (T2DM) patients with early chronic kidney disease (CKD), and explore its correlation with major adverse cardiovascular event (MACE) occurrence. Methods: This study enrolled patients with asymptomatic T2DM complicated with early CKD. Then, 4D-Auto LAQ was used to evaluate LA volume index (minimum, maximum, pre-ejection) and LA longitudinal and circumferential strains during each of the three LA phases: reservoir, conduit, and contraction. The primary endpoint for follow-up was defined as the first occurrence of nonfatal acute myocardial infarction, stroke, congestive heart failure, or cardiac death. Univariate and multivariate Cox proportional hazard analyses were used to evaluate the correlation between LA parameters and the MACEs in T2DM patients with early CKD. Results: A total of 361 patients were analyzed (mean age, 59.51 ± 11.17 years). During a median follow-up period of 47 months (interquartile range, 17–59 months), MACEs occurred in 70 patients. After adjusting for various clinical and echocardiographic predictors, increased LA volume and impaired reservoir function (ResF) were each independently associated with the primary endpoint: Left atrium minimum volume index (LAVImin) had an adjusted hazard ratio (HR) of 1.21 (95% confidence interval (CI), 1.08–1.35; p = 0.010), whereas left atrium longitudinal strain during the reservoir phase (LASr) had an adjusted HR of 0.81 (95% CI, 0.74–0.89; p < 0.001). Univariate and multivariate Cox regression analyses indicated that the cumulative incidence of MACEs was significantly greater in patients with LAVImin >16.9 mL/m2 than in those with LAVImin ≤16.9 mL/m2 (HR, 2.25; 95% CI, 1.03–6.39; p = 0.005). Furthermore, patients with a LASr <18.5% faced a markedly elevated risk of MACEs—nearly fourfold greater than individuals with a LASr ≥18.5% (HR, 3.95; 95% CI, 1.76–8.86; p < 0.001). Conclusions: An enlarged left atrium (LAVImin) and impaired ResF (LASr) are strongly associated with long-term outcomes in T2DM patients complicated with early CKD. LASr showed the strongest associations with the occurrence of MACEs.